2022
DOI: 10.1002/er.7786
|View full text |Cite
|
Sign up to set email alerts
|

A correlation to predict the thermal conductivity of MXene‐silicone oil based nano‐fluids and data driven modeling using artificial neural networks

Abstract: Summary In this article, MXene nano‐material is used with silicone oil to improve the thermal conductivity of nano‐fluids and it further increases the heat transfer. MXene nano‐material‐silicone oil‐based nano‐fluids have the capacity to be employed as heat transfer fluids in various thermal applications since it has excellent thermal properties, higher heat resistance and silicone oil have the ability to operate upto a temperature of 400°C. This paper investigates the thermal conductivity values for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… Refs. # Input(s) # Output(s) # of data points # of hidden layers # of neurons R 2 [ 63 ] 3 1 128 2 [6,6] 0.9999 [ 64 ] 5 1 712 1 18 0.9930 [ 65 ] 7 1 715 2 [10,15] 0.99997 [ 66 ] 2 1 33 1 4 0.99687 [ 67 ] 4 1 185 2 [5,5] 0.95600 [ 40 ] 5 1 100 2 [5,10] 1.00000 [ 68 ] 2 1 28 2 [5,5] 0.99900 [ 69 ] 3 1 72 2 ...…”
Section: Svr Ann and Anfis Configurationsmentioning
confidence: 99%
“… Refs. # Input(s) # Output(s) # of data points # of hidden layers # of neurons R 2 [ 63 ] 3 1 128 2 [6,6] 0.9999 [ 64 ] 5 1 712 1 18 0.9930 [ 65 ] 7 1 715 2 [10,15] 0.99997 [ 66 ] 2 1 33 1 4 0.99687 [ 67 ] 4 1 185 2 [5,5] 0.95600 [ 40 ] 5 1 100 2 [5,10] 1.00000 [ 68 ] 2 1 28 2 [5,5] 0.99900 [ 69 ] 3 1 72 2 ...…”
Section: Svr Ann and Anfis Configurationsmentioning
confidence: 99%
“…Aslfattahi et al 19 prepared PEG/water/MXene nanofluids and studied thermal conductivity experimentally and they found that k nf augment of 23%–29% at 0.1 wt% and over 25°C–45°C. Boobalan and Kannaiyan 20 studied the MXene/silicon oil nanofluids thermal conductivity using artificial neural network and observed an augmented thermal conductivity values.…”
Section: Introductionmentioning
confidence: 99%